A Patient-Derived Xenograft Model for Venous Malformation - Schrenk, Sandra (J Vis Exp, 2020)
Venous malformation (VM) is a vascular anomaly that arises from impaired development of the venous network resulting in dilated and often dysfunctional veins. The purpose of this article is to carefully describe the establishment of a murine xenograft model that mimics human VM and is able to reflect patient heterogeneity. Hyper-activating non-inherited (somatic) TEK (TIE2) and PIK3CA mutations in endothelial cells (EC) have been identified as the main drivers of pathological vessel enlargement in VM. The following protocol describes the isolation, purification and expansion of patient-derived EC expressing mutant TIE2 and/or PIK3CA. These EC are injected subcutaneously into the back of immunodeficient athymic mice to generate ectatic vascular channels. Lesions generated with TIE2 or PIK3CA-mutant EC are visibly vascularized within 7–9 days of injection and recapitulate histopathological features of VM patient tissue. This VM xenograft model provides a reliable platform to investigate the cellular and molecular mechanisms driving VM formation and expansion. In addition, this model will be instrumental for translational studies testing the efficacy of novel drug candidates in preventing the abnormal vessel enlargement seen in human VM.